2018
DOI: 10.1007/s42000-018-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in stress responses: a critical role for corticotropin-releasing factor

Abstract: Rates of post-traumatic stress disorder, panic disorder, and major depression are higher in women than in men. Another shared feature of these disorders is that dysregulation of the stress neuropeptide, corticotropin-releasing factor (CRF), is thought to contribute to their pathophysiology. Therefore, sex differences in responses to CRF could contribute to this sex bias in disease prevalence. Here, we review emerging data from non-human animal models that reveal extensive sex differences in CRF functions rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 121 publications
7
77
0
1
Order By: Relevance
“…In rodents, sex differences have been found in every aspect of CRF function from the inputs that regulate CRF neurons to CRF's postsynaptic efficacy (for review, see Bangasser & Wiersielis, ). In the PVN, there are several reports that female rats had greater CRF expression than males (Duncko, Kiss, Skultetyova, Rusnak, & Jezova, ; Viau et al, ), although this difference was not found in every rat study or with the Crh‐IRES‐Cre::Ai14 (tdTomato) reporter mouse (Sterrenburg et al, ; Walker, Cornish, Lawrence, & Campbell, ).…”
Section: Sex Differences In the Crf Systemmentioning
confidence: 99%
“…In rodents, sex differences have been found in every aspect of CRF function from the inputs that regulate CRF neurons to CRF's postsynaptic efficacy (for review, see Bangasser & Wiersielis, ). In the PVN, there are several reports that female rats had greater CRF expression than males (Duncko, Kiss, Skultetyova, Rusnak, & Jezova, ; Viau et al, ), although this difference was not found in every rat study or with the Crh‐IRES‐Cre::Ai14 (tdTomato) reporter mouse (Sterrenburg et al, ; Walker, Cornish, Lawrence, & Campbell, ).…”
Section: Sex Differences In the Crf Systemmentioning
confidence: 99%
“…This could be due to female mice having naturally higher baseline corticosterone than males (e.g., Malisch et al, 2007), which we cannot test given that not all of our serum samples were taken quickly enough (limit is 2-3 min). Another possibility is that females are more sensitive to human presence or to the stress of being captured, which would fit with findings in other species of a sex difference in glucocorticoid production in response to stressors (reviewed in Bangasser and Wiersielis, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…Numerous sex differences have been reported in the functioning of the stress neuropeptide, corticotropin-releasing factor (CRF), with differences in receptor expression, distribution, trafficking and signaling (reviewed in (Bangasser & Wiersielis, 2018)). The majority of these differences lead to enhanced CRF efficacy in females, which may lead to heightened sensitivity to stressors in females.…”
Section: Discussionmentioning
confidence: 99%